SPIRITUALITAS PENGHAYAT AJARAN KAPRIBADEN - Siti Fauziyah (UIN Sunan Kalijaga Yogyakarta, 2014)
This paper explores spiritual practices of a Javanese Spiritual Groups in Purworejo, Central Java, namely Kapribaden. Most of the Kapribaden practitioners are religious people who are not satisfied with their own religion and seek a spiritual path that is able to fulfil their spiritual thirstiness in order to find the meaning of life. According to the Kapribaden teaching , the meaning of life can attained be through three ways: First is working hard with responsibility and then receive the result sincerely; second, to behave to others with right action and love; and third, to take spiritual lessons from ever y calamity and suffering through intro- spection for their future better.